CRP and HS-CRP as a risk indicator in chronic non-transmissible diseases: a systematic review - Westphal, Greice (2021)
Introduction: Low-grade systemic inflammation underlies many diseases, including obesity, type 2 diabetes, hypertension and vascular disease. In this sense, and because it is considered the most promising biomarker in chronic health conditions, the high sensitivity C-reactive protein (hsCRP) has been gaining prominence in the scientific literature in the evaluation of several non-communicable chronic diseases (NCDs). Thus, the aim of this study was to analyze studies that have used CRP or hsCRP as a risk indicator.Material and Methods: For this purpose, a systematic review was carried out on the SCIELO database, restricting the search to national studies, with the descriptors “Protein C Reactive”, “ High-Sensitivity Protein C Reactive “ and “Protein C Reactive Ultra-Sensitive”.Results: After applying the selection criteria that included studies with human beings, with chronic diseases and with CRP or hsCRP values presented by group, 17 articles were analyzed, with a total of 12,493 participants. In general, the results of the studies reinforce the usefulness of CRP in the diagnosis, prognosis and treatment effect in all the studies analyzed.Conclusion: It is concluded, therefore, that hs-CRP has diagnostic value in several chronic health conditions, however some precautions must be observed for the appropriate use of this information.